Rekonstruksi Teologis Makna Kepenuhan Baptisan Roh Kudus dalam Dialog Pentakostal dan Injili - Rini Adiyati (P3M STT Kristus Alfa Omega, 2026)
Different understandings of the infilling of the Holy Spirit and the baptism of the Holy Spirit remain significant issues in pneumatological discourse, particularly in the dialogue between Pentecostal and Evangelicaled traditions. Previous studies have tended to discuss these two concepts denominationally, descriptively, or separately between the narrative approach of Acts and the doctrinal approach of the Pauline letters. This article aims to reconstruct the theological meaning of the infilling of the Holy Spirit and the baptism of the Holy Spirit through a hermeneutical dialogue between Pentecostal and Evangelicaled traditions. This study employs theological library research using historical-theological, hermeneutical, and comparative-constructive approaches to Acts, the Pauline letters, the Gospel of John, and classical and contemporary pneumatological literature. The findings show that the infilling of the Holy Spirit refers to the continuing work of the Spirit in repentance, spiritual renewal, sanctification, and the believer’s witness. The novelty of this article lies in its integrative theological synthesis, which understands the infilling of the Holy Spirit and the baptism of the Holy Spirit as two related but non-identical pneumatological categories. This article contributes to pneumatological studies and constructive theological dialogue across church traditions.